Evaluating Students’ Acceptance of Augmented Reality in Protist Learning: A Preliminary Research in Developing Protist Learning Media - Kusmahardhika, Noviansyah; Mahanal, Susriyati; Balqis, Balqis; Sulfa, Devi Mariya; Salim, Fitrah Amalia; Manalu, Marison Sudianto (JURNAL EKSAKTA PENDIDIKAN (JEP), 2024)
Protist concepts pose significant challenges for students due to their abstract nature and the complexity of microscopic structures. This study evaluates the validity, practicality, and acceptance of the Augmented Reality-Based Protist Application (AR-BPA), designed to enhance students' understanding of protists through immersive, 3D visualization. Following the development model by Lee & Owens (2004), this research focuses on the development stage, involving validity tests, preliminary implementation, and practicality assessments. Data were gathered from 3 experts, 32 students, and 2 lecturers through questionnaires and interviews, revealing high levels of usability and practicality for AR-BPA. The findings indicate that AR-BPA effectively supports student learning by making abstract concepts more accessible. Nonetheless, improvements in content scope and interface design are suggested to further optimize user experience. The study highlights AR-BPA’s potential to revolutionize protist education, with implications for broader applications in biology learning. Future research should explore scalability and additional factors to fully realize AR-BPA’s educational impact.